Impact of cooking and drying operations on color, curcuminoids, and aroma of Curcuma longa L. Issue 5 (23rd April 2022) - Yin, Molika; Weil, Mathieu; Avallone, Sylvie; Lebrun, Marc; Conejero, Geneviève; In, Sokneang; Bohuon, Philippe
Abstract: Effects of cooking and drying on color, curcuminoids, essential oil, and aroma compounds of Curcuma longa L. were assessed. Sliced fresh turmeric rhizomes were air‐dried at 60°C directly or after cooking at 95°C for 3 or 90 min. Microscopic observations showed that curcuminoids and essential oil are located in different dedicated cells. Curcuminoids and essential oil of dried turmeric were both around 10% db. After processing, curcuminoids were dispersed throughout the matrix. Drastic cooking and drying operations decreased chromatic values more than smooth cooking. Cooking had no impact on curcuminoid and essential oil contents and slightly modified the aromatic profile of essential oils. Drying decreased the curcuminoid (<38%) and essential oil (<13%) contents. Turmeric starchy matrix preserves the curcuminoids and essential oil during the process. We recommend a preliminary smooth cooking step to reduce the drying time, save energy consumption and preserve turmeric quality. Novelty impact statement: Our study brings us to propose better practices for turmeric processing. A smooth cooking (95°C/3 min) before drying is recommended to preserve the quality of the turmeric as the curcuminoids and essential oil are preserved during cooking. This protection could be linked to the starchy structure of the turmeric matrix.